2018
DOI: 10.3390/electronics7080137
|View full text |Cite
|
Sign up to set email alerts
|

A Pipelined FFT Processor Using an Optimal Hybrid Rotation Scheme for Complex Multiplication: Design, FPGA Implementation and Analysis

Abstract: Abstract:The fast Fourier transform (FFT) is the most prevalent algorithm for the spectral analysis of acoustic emission signals acquired at ultra-high sampling rates to monitor the condition of rotary machines. The complexity and cost of the associated hardware limit the use of FFT in real-time applications. In this paper, an efficient hardware architecture for FFT implementation is proposed based on the radix-2 decimation in frequency algorithm (R2DIF) and a feedback pipelined technique (FB) that allows effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Nguyen et al [21] suggested a R2DIF algorithm. In this algorithm, the shift registers were utilised to share data between the input and output ports in a feedback pipeline method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nguyen et al [21] suggested a R2DIF algorithm. In this algorithm, the shift registers were utilised to share data between the input and output ports in a feedback pipeline method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…After demodulation, the I/Q components are processed through spectral estimation to detect f d . The spectral analysis is performed through the efficient Fast Fourier Transform (FFT) [25][26][27] or more sophisticated adaptive estimators [28][29][30]. The demodulated ultrasound echoes are typically organized in the memory of the processing system along the columns of a matrix.…”
Section: Pulse Wave Signals In Industrial Echo-doppler Applications Amentioning
confidence: 99%
“…Therefore, it is possible to compute moving distances and rotation angles of robotic systems in a short time. Recently, energy-efficiency/area-efficiency strategy was the crucial methodology in hardware design [7][8][9][10][11]. In [7], an energy-efficiency design of an image processing technique was proposed for wireless sensor networks.…”
Section: Introductionmentioning
confidence: 99%
“…An area-efficient, two-dimensional interpolation architecture based on cubic convolution was proposed in [10], which was developed to calculate the square-root function. In [11], the authors proposed an efficient hardware architecture for fast-Fouriertransform (FFT) implementation where the modified CORDIC (m-CORDIC) algorithm was employed to replace the complex multipliers to reduce complexity significantly.…”
Section: Introductionmentioning
confidence: 99%